2011
DOI: 10.1111/j.1600-0706.2010.19202.x
|View full text |Cite
|
Sign up to set email alerts
|

Crab herbivory regulates re‐colonization of disturbed patches in a southwestern Atlantic salt marsh

Abstract: Recent work exploring the effects of physical stress and herbivory on secondary succession in estuarine plant communities agrees with basic stress models and reveal that herbivory is an important force in brackish and oligohaline marshes but negligible in physically stressful salt marshes. In these systems, herbivores are terrestrial, and thus negatively affected by the same stressful factors that affect marsh plants (i.e. frequent flooding or high salinities). We evaluated the effects of a marine herbivore (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 69 publications
(102 reference statements)
2
20
0
Order By: Relevance
“…This process of grazer‐driven expansion of vegetation die‐off along die‐off borders, often driven through the formation and movement of consumer fronts along the edges of remaining plant prey populations, has also been observed in marsh die‐off areas in Argentina (Daleo et al . ), the southeastern USA (Silliman et al . ) and New England (Altieri et al .…”
Section: Discussionmentioning
confidence: 99%
“…This process of grazer‐driven expansion of vegetation die‐off along die‐off borders, often driven through the formation and movement of consumer fronts along the edges of remaining plant prey populations, has also been observed in marsh die‐off areas in Argentina (Daleo et al . ), the southeastern USA (Silliman et al . ) and New England (Altieri et al .…”
Section: Discussionmentioning
confidence: 99%
“…Succession models have been proposed for many salt marshes from the Northern Hemisphere, where the recovery of disturbance-generated bare areas occurs within 3 yr (Pennings & Bertness 2001). In the Southern Hemisphere, however, previous observations revealed that bare patches found on the southwestern (SW) Atlantic Mar Chiquita coastal lagoon (37°44' S, 57°26' W, Argentina) remain almost unchanged for more than 4 yr (Daleo et al 2011). Thus, the aim of our study was to determine which biological and physical factors condition the colonization of bare patches in a SW Atlantic salt marsh.…”
Section: Introductionmentioning
confidence: 90%
“…As was proposed in our first hypothesis, the dispersal of S. perennis seeds from adult individuals could be a strong environmental filter that limits colonization in these marshes and thereby delays secondary succession. In this context, the existence of a Spartina densiflora matrix might be acting as a natural barrier for seed dispersal, given that bare patches and Sarcocornia perennis plants occur sparsely within this matrix (Daleo et al 2011).…”
Section: Seed Availabilitymentioning
confidence: 99%
See 2 more Smart Citations